Competing Bids, Target Management Resistance, and the Structure of Takeover Bids - Jennings, Robert H.; Mazzeo, Michael A. (Review of Financial Studies, 1993)
We examine the structure of initial takeover bids and the frequency of observing competing bids and target management resistance. We find the use of cash is not consistently correlated with the frequency of competition or resistance and that the cost of acquiring information about a target is associated with the likelihood of competition and resistance. A high bid premium appears to deter competing offers and is also associated with a lower likelihood of resistance. Finally, target management resistance is associated with an increased likelihood of a competing offer arising and a larger increase in target shareholder wealth between the initial public announcement and outcome dates relative to the not-resisted subsample for both successful and unsuccessful acquisition proposals.